Back to the future: Exploring riverine macroinvertebrate communities' invasibility. (19th April 2022) - Guareschi, Simone; Wood, Paul J.; England, Judy; Barrett, Jon; Laini, Alex
Abstract: Riverine communities have been subject to numerous biological invasion events, with crustaceans among the most successful group of invasive animals worldwide. Understanding what makes a river system prone to invasion is of considerable interest to environmental regulators, resource managers, scientists and wider society globally. The Ponto‐Caspian amphipod, Dikerogammarus haemobaphes (Crustacea: Gammaridae), is a hyper‐successful invasive species that was first recorded in the UK in 2012. The use of contemporary distribution data for D. haemobaphes (2009–2020) from England provided a unique opportunity to study faunal community patterns and differences between sites that experienced invasion compared to those that have not. Macroinvertebrate community taxonomic, functional and phylogenetic features, as well as the presence of co‐occurrent invaders and abiotic features of the river systems, were examined from sites before the invasion and compared to control sites that were not invaded during the study period. Sites that would later experience invasion by D. haemobaphes were characterized by higher abundances of other invaders (e.g., especially Ponto Caspian taxa), lower abundances of crustaceans and typically had greater channel width and water depth. These basic characteristics may help identify sites at risk of future invasion by D. haemobaphes . Most biomonitoring tools examined displayed no difference between control and pre‐invaded samples, while both taxonomic and functional richness displayed higher values at sites that were subsequently invaded, questioning classic biological invasion hypotheses. Recognizing specific community characteristics that may be a precondition for subsequent invasion is essential for understanding and better predicting their future trajectories of change.